Peran ilmu Al-qur’an dalam membentuk modernisasi beragama - Sapphire, Cady Nisrina (Maliki Interdisciplinary Journal, 2025)
Modernization brings changes in the way humans understand religious values, including within Islamic traditions. Amid rapid social change, Qur'anic knowledge serves as a foundation for maintaining the relevance of Islamic teachings without abandoning their fundamental values. Through branches such as tafsir, asbabun nuzul, and balaghah, quranic knowledge enable as contextual understanding of quranic verses, thus remaining able to addres the challenges of the times, such as issue of social justice, scine, and digital ethic. This study discusses how quranic knowledge encourages religious modernization through the intergration of revelation and reason a rational interpretative approach, and a renewal of people’s prespectives on education, social, life, and tecnological developments. The result of the study indicate that religious modernization is not an attemp to replace the core teaching, but rather to update the way they are understood to align with the needs of contemporary society. With a correct understanding of quranic knowledge, modernization can proceed harmoniously without losing the core teaching of islam.